Radicalisation and paramilitary culture: the case of Wanndy’s Telegram groups in Malaysia - El-Muhammady, Ahmad; Wan Daud, Murni (Springer, 2021)
Many studies have shown that the factors and pathways to radicalisation are multivariate, with social media being a key resource that terrorists use to expand their influence. In the context of Malaysia’s Special Branch Counter Terrorism Division revealing that 98% of terrorist supporters and members in the country were recruited online, this chapter examines a case study of two Islamic State Telegram groups which was established by Wanndy, South-East Asia’s most effective terrorist recruiter. Analysing text from the actual Telegram conversations, the chapter outlines how the radicalisation process was carried out in this private, virtual environment, and the crucial role that paramilitary themes played in romanticising jihad and formation of a terrorist’s mind. The findings are outlined in relation to a five-step process towards extremism: trust building, mind formation, consensus building, affirmation of support and actualisation.